DOSTOEVSKY, BAKHTIN, POLYPHONIC NOVEL (Scientific journal of the Fergana State University, 2024)
The article analyzes the artistic skills of F.Dostoevsky, the founder of the polyphonic novel. The writer's philosophical, psychological or socio-psychological novels such as "Crime and Punishment", "The Brothers Karamazov", "The Madman" received their objective assessment as a result of M. Bakhtin's research. As a result of the new perception of reality, the world, the inner experiences of the hero in the creative psychology of "thinking differently", which Dostoevsky himself recognized, the sudden resounding of different thoughts, experiences and views creates multi-voicedness and multi-layeredness in the structure of the work. It is this new way of thinking and its artistic interpretation that is fundamentally different from the artistic features of the poetics of philosophical and psychological novels. As a result of Dostoevsky's artistic and aesthetic innovation, a new model of artistic observation of the universe, the human psyche, emerged. M.Bakhtin expressed a firm opinion that a one-sided interpretation of the author's novels "monologizes his polyphonic poetics." The literal human inner world, which F.Dostoevsky raised to the level of perfect interpretation, its existence in reality is the result of the influence of polyphonic interpretation. If the term "polyphonic poetics" means the poetics of a polyphonic novel, the concept of "appearance of polyphony in the poetics of a novel" means that a polyphonic interpretation appears in some cases in a non-polyphonic novel. The duplicity characteristic of polyphony is one of the most frequently manifested polyphonic artistic components. The polyphonic novel as an artistic phenomenon had a positive effect on the literary process: it was manifested in the interpretation of consciousness in modern novels, in the experiences of the heart and soul in realistic novels, and led to the synthesis of genres in the later periods of the dynamics of the novel genre.